On Coupled Klein-Gordon-Schrödinger Equations with Acoustic Boundary Conditions. (15th September 2010) - Ha Ha, Tae Gab Tae Gab; Park Park, Jong Yeoul Jong Yeoul
Abstract : We are concerned with the existence and energy decay of solution to the initial boundary value problem for the coupled Klein-Gordon-Schrödinger equations with acoustic boundary conditions.